MOLECULAR DYNAMICS SIMULATION OF THE ADSORPTION PHENOMENON OF (2-ETHYLHEXYL) PHTHALATE (DEHP) ON MONTMORILLONITE - Ro'isatul Umma, Reza
Di (2-ethylhexyl) phthalate (DEHP) is one of the pollutants designated by the Europian Union (EU) and the World Health Organization (WHO) as the main pollutant list and considered the most problematic for human health, which can cause disruption of the endocrine system, the neuroprotective, hepatotoxic, and cardiotoxic. DEHP is widely used as a plasticizer especially in polyvinyl chloride (PVC), polyethylene, and polypropylene products which contain almost 50% DEHP. DEHP compounds are not covalently bonded with their products so they are easily released from the product and can enter the water, air, or soil environment. The amount of DEHP in a free environment needs to be controlled and one of the methods is by means of adsorption which is considered simple to do, energy efficient and cost effective. In this study, the adsorption process was carried out using a molecular approach by molecular dynamics simulation using GROMACS software to see the microscopic interactions of DEHP compounds with montmorillonite as the adsorbent. Molecular dynamics simulations complement conventional experiments, which are able to present molecular structures and interactions at the microscopic level, accurately calculate intra- or intermolecular potentials, and dynamically evaluate configuration and quantity properties. In this study, the surface modification of montmorillonite was also carried out with cationic surfactants, namely cetyl trimethyl amonium (CTMA) and N, N'-Bis (dodecyldimethyl) -1,2-ethanediamonium (BDED), which were later referred to as organo- montmorillonite. This modification aims to increase the adsorption strength of DEHP. Based on the simulation results, the initial concentration (C0) of 0.044 mol / L DEHP resulted in the maximum adsorption of 77.5%. When C0 DEHP was increased to 0.088 mol / L, the adsorption on the MMT surface without modification only reached 1.25%. Whereas in the BDED-modified MMT (1 layer) with the number of BDED molecules equal to 0.24 CEC and simulated at the same temperature, namely 300 K, the adsorption percentage has increased to 44%. This shows that the addition of cationic surfactants succeeded in increasing the adsorption percentage of DEHP because the addition of this surfactant was able to expand the space between the layers of montmorillonite so that the adsorption sites were increasing. The N atom of the cationic surfactant binds to the siloxane montmorillonite surface, while the C chain of the cationic surfactant binds to DEHP. In addition, the use of two layers of montmorillonite is more effective than one layer and the use of BDED cationic surfactant as a modifier gives better results than CTMA.